Label-Free Target Identification Reveals the Anticancer Mechanism of a Rhenium Isonitrile Complex - Yim, Junhyeong; Park, Seung Bum (Frontiers in Chemistry, 2022)
Elucidation of the molecular mechanism of therapeutic agents and potential candidates is in high demand. Interestingly, rhenium-based complexes have shown a highly selective anticancer effect, only on cancer cells, unlike platinum-based drugs, such as cisplatin and carboplatin. These differences might be attributed to their different molecular targets. We confirmed that the target of tricarbonyl rhenium isonitrile polypyridyl (TRIP) complex is a protein, not DNA, using ICP-MS analysis and identified heat shock protein 60 (HSP60) as its target protein using a label-free target identification method. The subsequent biological evaluation revealed that TRIP directly inhibits the chaperone function of HSP60 and induces the accumulation of misfolded proteins in mitochondria, thereby leading to the activation of mitochondrial unfolded protein response (mtUPR)-mediated JNK2/AP-1/CHOP apoptotic pathway.